Актуальные вопросы профессионального и трудового самоопределения сельской молодежи - Чигрин, В. (Социология: теория, методы, маркетинг, 2007)
The author discusses the question of the state and society's influence on the professional and work self-determination among village youth in Ukraine. Moreover, major tasks and principles of youth policy in the context of urgent needs relating to development of the Ukrainian agro-industrial complex are examined.